Atomic oxygen assisted CO2 conversion: A theoretical analysis. (January 2023) - Verheyen, C.; van 't Veer, K.; Snyders, R.; Bogaerts, A.
Abstract: With climate change still a pressing issue, there is a great need for carbon capture, utilisation and storage (CCUS) methods. We propose a novel concept where CO2 conversion is accomplished by O2 splitting followed by the addition of O atoms to CO2 . The latter is studied here by means of kinetic modelling. In the first instance, we study various CO2 /O ratios, and we observe an optimal CO2 conversion of around 30–40% for 50% O addition. Gas temperature also has a large influence, with a minimum temperature of around 1000 K to a maximum of 2000 K for optimal conversion. In the second instance, we study various CO2 /O/O2 ratios, due to O2 being a starting gas. Also here we define optimal regions for CO2 conversion, which reach maximum conversion for a CO2 fraction of 50% and an O/O2 ratio bigger than 1. Those can be expanded by heating on one hand, for low atomic oxygen availability, and by quenching after reaction on the other hand, for cases where the temperatures are too high. Our model predictions can serve as a guideline for experimental research in this domain. Highlights: A new approach to CO2 conversion, based on mixing CO2 gas with O atoms. Chemical kinetics modelling study into the addition of CO2 to a dissociated oxygen gas. The optimum for conversion was found at around 50% CO2 addition.